Answer:
(x, y) = (-1, 2)
Explanation:
Substitution is easier if you already have an expression for the variable you want to make a substitution for. Here, we don't have that, but we have an equation with x having a coefficient of 1. We can use that to write an expression for x:
x = 3 -2y . . . . . subtract 2y from both sides of the second equation
5(3 -2y) +3y = 1 . . . . substitute for x in the first equation
15 -10y +3y = 1 . . . . . eliminate parentheses
-7y = -14 . . . . . . . . . . subtract 15, collect terms
y = 2 . . . . . . . . . . . . . divide by -7
Use this value in the equation for x:
x = 3 -2(2) = -1
The solution is (x, y) = (-1, 2).